Parameter sensitivity in nonlinear transient thermal problems - Kleiber, Michał; Slużalec, Andrzej (Computer Assisted Methods in Engineering and Science; Vol 2 No 4 (1995), 2023)
A general problem of parameter sensitivity of non-linear transient thermal systems is considered. The non-linear sensitivity path is followed by a weighted residual method employing the continuum description. The resulting finite element equations are derived. Both the direct differentiation and adjoint system methods are employed to evaluate sensitivity functional increments during the integration time step. Numerical results illustrate the method proposed.